Lipid profiles of Nigerians living with type 2 diabetes mellitus: A systematic review and meta-analysis - Azeez, Taoreed; Adio, Mosunmoluwa; Bamidele, Olabisi (Journal of Diabetes and Endocrine Practice, 2021)
Introduction: Dyslipidemia is often associated with type 2 diabetes (T2D), with both having an additive effect on cardiovascular risk. The objective of the meta-analysis was to determine the prevalence of dyslipidemia in individuals living with T2D mellitus in Nigerian and to examine the pattern of their dyslipidemia. Methods: The study followed the preferred reporting items for systematic reviews and meta-analyses guidelines. Medical databases such as PubMed, Google Scholar, African Journals Online, and SCOPUS as well as the gray literature were systematically searched. MetaXL was used for statistical analysis adopting the random effect model. Heterogeneity was determined using the I2 statistic, while publication bias was assessed with the funnel plot. Results: Twenty-two studies met the eligibility criteria for the meta-analysis. The total sample size was 3575. The prevalence of dyslipidemia among Nigerians living with diabetes ranges from 25% to 97.1%. The pooled prevalence of dyslipidemia among Nigerians living with T2D was 63% (95% confidence interval [CI]: 52%–72%). I2 statistic was 97%. The funnel plot implied minimal publication bias. The pooled prevalence of elevated low-density lipoprotein cholesterol was 33% (95% CI: 18%–49%). The pooled prevalence of elevated hypertriglyceridemia was 88% (95% CI: 84%–91%). The pooled prevalence of low high-density lipoprotein cholesterol (HDL-C) was 47% (95% CI: 32%–62%). The pooled prevalence of elevated hypercholesterolemia was 33% (95% CI: 23%–43%). Conclusions: The prevalence of dyslipidemia among Nigerians with T2D mellitus is very high. The most common abnormalities are hypertriglyceridemia and low HDL-C.
Keywords: Dyslipidemia; hypercholesterolemia; lipid profile; Nigeria; prevalence; type 2 diabetes